Effect of Carbon Fiber Admixture and Length on Microwave Deicing Efficiency of Airport Road Surface Concrete - Yi-peng Ning; Jin-yu Xu; He Huang; Zhi-hang Wang; Ao Yao (Advances in Materials Science and Engineering)
In order to improve the microwave deicing efficiency of airport road surface concrete, the method of incorporating carbon fiber materials of different doping amounts and lengths into concrete is proposed. The test method is optimized by using a fiber-optic temperature sensor and a self-developed open microwave deicing vehicle, and the effect of the coupling effect of different carbon fiber doping and length on the microwave deicing efficiency of concrete is studied. The results of the study show that the appropriate amount of carbon fiber blended into the concrete can significantly improve the microwave deicing efficiency, and the reasonable use of carbon fiber-modified concrete can achieve the purpose of efficient deicing of the airport road surface. By analyzing the temperature rise curve, temperature rise rate curve, deicing effect, and infrared thermography of the microwave deicing process, combined with the “heat generation-heat dissipation” theory, the microwave deicing is divided into four stages: concrete wave absorption, water layer formation, ice thinning, and ice breaking and ice melting. In the process of microwave deicing of concrete, changing the length of carbon fiber and the amount of doping will have a greater impact on the rate of temperature rise and deicing range, but the shape of deicing remains basically the same, mainly spindle-shaped. When the length of carbon fiber is short, it is not conducive to the absorption of microwave by concrete, and with the increase of fiber length and doping amount, the wave absorption performance of carbon fiber-modified concrete on the airport road surface is gradually improved; when the fiber length is 0.6 cm and the fiber doping amount is 2‰, the wave absorption performance is the best, and the deicing rate is 1.82 times of ordinary concrete, and the deicing area is 1.2 times of ordinary concrete.